Pengaruh Bantuan Sosial (BANSOS) terhadap Pengurangan Kemiskinan di Indonesia Tahun 2015-2019 - Awaliyah Matondang, Khairani; Dwi Pratama, Vingky; Melody Sitorus; Yanti Situmorang, Eva Juli (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to determine the effect of social assistance on reducing poverty in Indonesia. The research method used is a quantitative method with data collection techniques obtained from BPS. The data analysis technique in this research uses the classic assumption test. The research results show that 1. Poverty in Indonesia from 2015 - 2019 has decreased. 2. Social assistance spending has a negative and not significant effect on the number of poor people in Indonesia.